Copyright and fair use practices [soundrecording] - North, William D.; Lieb, Charles; American Library Association. Conference (91st). (Los Angeles, Calif. CREDR Corp., 1973)
Presents the positions of both the AAP and ALA on copyrighted materials in libraries, the subject in general, pending copyright legislation, and the doctrine of "fair use".
American Library Association, 91st annual conference. Media: man, material, machine.
Moderator, Edmon Low
Keywords: Copyright -- Congresses; Fair use (Copyright) -- Congresses; Intellectual property; Library science